PREFERENSI DAN KONSUMSI RUMAH TANGGA TERHADAP BERAS ORGANIK DI KOTA BANDAR LAMPUNG - Gunawan, Bagus; Sayekti, Wuryaningsih Dwi; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The purpose of this study is to analyze preferences, consumption patterns, as well as factors that impacted household consumption of organic rice in Bandar Lampung City. The study method utilized was a survey. The selection of Bandar Lampung City as the study location was determined using the purposive method. Data collection was conducted in November 2023 - February 2024 with a total of 50 household respondents. Sampling was done by accidental sampling method at A, B, and C supermarkets. The data analysis utilized is multiattribute fishbein, descriptive analysis, as well as multiple linear regression. The results indicated that housewives aged 33-46 years with the latest education level of undergraduate make up the majority of household customers. The number of family members ranges from 3-4 people with an average total household income of IDR 7,610,000 per month. The preference of households in Bandar Lampung City for organic rice are favorabel. Most households consume organic brown rice with the Hotel brand. Make purchases 3-4 times a month with the size of the package purchased, which is 2 kg. The frequency of cooking is 7 times a week with an average consumption of 11.24 kg per month. The reason households consume organic rice is because of food safety factors. Factors that substantially impact the amount of household consumption of organic rice in Bandar Lampung City are the price of organic rice, the price of non-organic rice, household income, age, and taste. Key words:   consumption pattern, organic rice, preference